Rational design of functionalized covalent organic frameworks and their performance towards CO2 capture. Issue 37 (10th July 2019) - An, Shuhao; Xu, Ting; Peng, Changjun; Hu, Jun; Liu, Honglai
Abstract : Two new functionalized covalent organic frameworks containing carbazole and benzothiazole displayed excellent CO2 uptake. Abstract : We describe the design and synthesis of two new functionalized covalent organic frameworks, named Cz-COF and Tz-COF, by using monomers containing carbazole and benzobisthiazole as building blocks. The resultant materials possess high crystallinity, permanent porosities as well as abundant heteroatom activated sites in the framework. As solid adsorbents, both COFs exhibit excellent CO2 uptake (11.0 wt% for Cz-COF and 15.4 wt% for Tz-COF), high adsorption selectivity for CO2 over N2 and good recyclability.